Acute phase proteins and biochemical and oxidative stress parameters in Hypoderma spp. infested cattle - MERHAN, O.; BOZUKLUHAN, K.; GOKCE, H. I. (Journal of the Hellenic Veterinary Medical Society, 2018)
The aim of the present study was to determine concentrations of acute phase proteins (APP), oxidative stress and some biochemical parameters in naturally infested cattle with Hypoderma spp. For this purpose, 10 clinically healthy cattle as controls and 25 Brown Swiss cattle with Hypoderma spp. were used. Blood samples were collectedto tubes from jugular vein. Parts of blood samples were stored without any process as a whole blood. The serum was separated from the remaining blood samples. The reduced glutathione (GSH) in whole blood and the level of malondialdehyde (MDA), haptoglobin (Hp), ceruloplasmin, serum amyloid A (SAA), AST, GGT, ALP, CK, albumin, urea and total protein levels in serum were colorimetrically determined. The present study indicated that the concentrations of Hp, SAA, ceruloplasmin, AST, GGT, ALP, CK, and MDA were significantly increased, and albumin, total protein, GSH concentrations were significantly decreased in the Hypoderma spp. infested group compared to the control group. Additionally, the increase in serum Hp levels was proportional to the number of Hypoderma spp. and it was statistically significant. In conclusion, the production of APP increased in a response to acute phase response in animals with subcutaneous warbles. Furthermore, liver functions were also shown to be impaired and oxidative stress developed as a result of metabolic products of the parasite in Hypoderma spp. infested cattle.